ANALISIS KETERSEDIAAN TENAGA PERAWAT DI INSTALASI RAWAT JALAN RUMAH SAKIT UNIVERSITAS BRAWIJAYA - Siburian, Anggi Satria (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2024)
Availability Analysis of Outpatient Nurses in Universitas Brawijaya Hospital. The quality of nursing services is supported by the availability of sufficient workforce. Consequently, RSUB with a limited number of outpatient nurses needs to assess nurse staffing requirements based on workload. To determine the nurse availability in outpatient care based on workload. Workload measurements are carried out subjectively and objectively. Subjective measurement uses a workload questionnaire, while objective measurement employs the WISN method. The sample size is 20. Data collection involves interviews, observation and document study. Descriptive analysis is applied to the results of both measurements. Subjective measurements indicate a medium nurse workload, and the objective WISN ratio is 0.96, implying a need for one additional nursing staff member. Apart from recruiting the number of nurses, hospitals need to consider measuring other workloads analysis from different aspects in order to achieve a balance between the availability of the number of nurses and workload.